2018
DOI: 10.1016/j.procbio.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin partitioning from a clarified fermentation broth of Lactobacillus plantarum ST16Pa in aqueous two-phase systems with sodium sulfate and choline-based salts as additives

Abstract: The partitioning of bacteriocin, a promising alternative to chemical preservatives, in a novel inexpensive and stable aqueous two-phase system (ATPS) comprising poly(ethylene glycol) (PEG) and sodium polyacrylate (NaPA) was studied. The ATPS was generated by mixing both polymers with Na 2 SO 4 or choline chloride ([Ch]Cl) and a bacteriocin extract from the fermented broth of Lactobacillus plantarum ST16Pa. Bacteriocin showed stability at different pH values (3.0-8.0) and temperatures (50-80°C), as well as in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Some previous studies have shown that the negative charge of NaPA can interact with the oppositely charged sites of biomolecules through electrostatic interactions, destabilizing or changing their molecular structure and decreasing their biological activity [31,41]. However, at the concentrations studied, GFP maintained its fluorescence activity, which is consistent with previous findings obtained for clavulanic acid, where no significant losses of activity were observed after the exposure of the biomolecule to aqueous solutions of NaPA 8000 at 5 and 15 wt% [42].…”
Section: Gfp Fluorescence Stabilitysupporting
confidence: 90%
“…Some previous studies have shown that the negative charge of NaPA can interact with the oppositely charged sites of biomolecules through electrostatic interactions, destabilizing or changing their molecular structure and decreasing their biological activity [31,41]. However, at the concentrations studied, GFP maintained its fluorescence activity, which is consistent with previous findings obtained for clavulanic acid, where no significant losses of activity were observed after the exposure of the biomolecule to aqueous solutions of NaPA 8000 at 5 and 15 wt% [42].…”
Section: Gfp Fluorescence Stabilitysupporting
confidence: 90%
“…These results might have been due to removal of protein contaminants responsible for suppression of pediocin PA-1 antimicrobial activity or its inactivation. Likewise, Sabo et al (2018), using ATPS for bacteriocin partitioning from clarified broth of Lb. plantarum ST16Pa, demonstrated the potential of this system as an initial step for bacteriocin recovery and purification.…”
Section: Purification Of Bacteriocin St16 Obtained In Mrs Broth and Imentioning
confidence: 99%
“…Hence, the purification factor decreased with increasing the PEG molecular weight to 6000 and 8000 due to the excluded volume effect. Sabrina da Silva Sabo et al [12] reported that a low concentration of PEG could increase the purification factor of BLIS in an aqueous two phase system. Hence, 10% (w/w) of PEG 4000 with the highest purification factor was used in further experiments.…”
Section: Discussionmentioning
confidence: 99%